Cidadania e desenvolvimento: como anda a inclusão das pessoas com deficiência (PCD) no mercado de trabalho formal da Região Metropolitana de Salvador (RMS)? - OLIVEIRA, Érica Sousa Gonçalves de (2016)
The aim of this work is to present the standard inclusion of persons with disabilities (PWD) in the formal labor market in Salvador Metropolitan Area (RMS). To this end, initially comes some conceptual elements about human rights, development and citizenship, as well as affirmative action. Later presents the progress of legislation on the inclusion of PCD, regarding the Brazilian experience. Finally the statistical data on the inclusion of PCD in the RMS labor market will be analyzed. To realize this task, refers to data provided by the Population Census 2000 and 2010, as well as the Annual Social Information (RAIS) the years 2010 and 2013. The hypothesis that guides the construction of the arguments based on the idea of that despite the advances observed from the point of view of legislation to increase the participation of PWD in the labor market is still quite timid inclusion of these people in the aforementioned market.